The Association Between Autophagy and Ovarian Cancer - Şayeste Demirezen; Merve Özcan; Sinan Beksaç (Medical Network, 2012)
Ovarian cancer is the most common cause of cancer death in all gynecological cancers. The mortality of this cancer is high due to the fact that the symptoms of this disease does not occur until its advanced stage. Surgery, chemotherapy and radiation therapy are current cancer therapies for ovarian cancer. However the recent studies reported that autophagy also can be a novel therapeutic strategy for this cancer. Autophagy leads to cell death when it is activated excessively in the cell and so it can be used for the treatment of neoplastic or chemoresistant ovarian cancer cells. In this review, in order to understand the association between autophagy and ovarian cancer, we summarized the general characteristics of ovarian cancer, autophagy and the relationship between these two concepts.